Insurance and the Internet: evaluating the-business context of insurance companies in Greece - Πολλάλης, Γιάννης Α. (SPOUDAI Journal of Economics and Business, 2007)
One of the major promises of the Internet is to change the way business is done in a dramatic way. If this promise were to be fulfilled, the Internet would allow companies to integrate their businesses seamlessly. Further, these companies would have more information that could be retrieved at a much higher speed than before, which would serve to create possibilities for improving profits. When we consider developments over the last few years in Greece, we can see that insurance companies have encountered many problems in using the Internet effectively to fulfil this promise. This paper aims to increase awareness of opportunities for e-commerce in the insurance industry today and in the future. In this paper we first describe the state of the insurance market in Greece, paying attention to the key metrics that define the size and shape of the industry. Next we explore the e-business landscape in Greece and unveil the relations between the internet and insurance practice. Also, we refer to companies’ capabilities to support the modernization movement and e-Business initiatives that are changing the insurance industry. We further examine the areas in which we believe technology will have the greatest impact on the industry. Finally, we delineate the e-insurance presence and profile of the insurance companies in Greece through the evaluation of their web sites, using various criteria. At the end, the frame of a web strategy is suggested in order insurers in Greece to take the lead in moving the insurance industry into 21st century technology capabilities. JEL Classifications: G22, O32, L86